Regioselective Synthesis of 4‐Nitro‐ or 4‐Chloro‐Tetrasubstituted Pyrazoles from Hydrazones and β‐Halo‐β‐nitrostyrenes. Issue 2 (29th October 2013) - Deng, Xiaohu; Liang, Jimmy T.; Mani, Neelakandha S.
Abstract: We report an acid‐catalyzed cycloaddition reaction of hydrazones with β‐bromo‐ or β‐chloro‐β‐nitrostyrenes for the regioselective synthesis of 4‐nitro‐ or 4‐chloro‐tetrasubstituted pyrazoles. Arising from a common 4‐halo‐4‐nitropyrazolidine intermediate, the identity of the pyrazole product formed is dependent on the relative leaving group abilities of the halo and nitro substituents. Abstract : We report an acid‐catalyzed cycloaddition reaction of hydrazones with β‐bromo‐ or β‐chloro‐β‐nitrostyrenes for the regioselective synthesis of 4‐nitro‐ or 4‐chloro‐tetrasubstituted pyrazoles. The product formed is dependent on the relative leaving group abilities.